Genome-wide analysis of iron-regulated transporter 1 (IRT1) genes in plants - ÖZYİĞİT, İBRAHİM İLKER (KOREAN SOC HORTICULTURAL SCIENCE, 2015)
Iron (Fe) is an essential micronutrient required in a number of biological processes in plant species. Fe transporters are a type of broad-range metal transporter and have different families functioning in different compartments. This study focused on iron-regulated transporter 1 (IRT1), which are mainly responsible for Fe uptake from root, in 17 selected plant species with an emphasis on Brachypodium distachyon, Chlamydomonas reinhardtii, Solanum lycopersicum and Populus trichocarpa species. All IRT1 proteins were observed to belong to the ZIP (PF02535) protein family with eight transmembrane (TM) domains, and have a similar molecular weight (33.86-42.72 kDa, except for C. reinhardtii with 65.83 kDa) and amino acid length (324-408 aa, except for C. reinhardtii with 639 aa), with pI values of 5.31-7.16. The sub-cellular localization of these proteins was predicted to be the plasma membrane. Similar exon numbers were also detected with most genes having 2-3, except for C. reinhardtii (5), Physcomitrella patens (5) and Vitis vinifera (4). In a phylogenetic tree, monocot-dicot separation was not observed in main groups but some subgroups included only monocot or dicot proteins. Predicted interaction partner analysis of AtIRT1 (AT2G30080.1) pointed to main interaction partners either directly related with iron transport or that of other metal ion. The results of this study provide a theoretical reference for elucidating the structural and biological role of IRT1 genes/proteins in plant species.
Keywords: chelate; micronutrient; redox reaction; reactive oxygen species; transmembrane topology; ARABIDOPSIS-THALIANA; METAL TRANSPORTER; SYNTHASE GENES; ZIP FAMILY; PROTEIN; CADMIUM; PHYTOSIDEROPHORES; TRANSLOCATION; CLONING; RICE